Trends in the use of partial nephrectomy for cT1 renal tumors: Analysis of a 10-yr European multicenter dataset. Issue 11 (November 2016) - Simone, G.; De Nunzio, C.; Ferriero, M.; Cindolo, L.; Brookman-May, S.; Papalia, R.; Sperduti, I.; Collura, D.; Leonardo, C.; Anceschi, U.; Tuderti, G.; Misuraca, L.; et al.
Abstract: Aim: Although extensively addressed in US registries, the utilization rate of Partial Nephrectomy has been poorly addressed in European settings. Our aim is to evaluate the impact of hospital volume on the use of PN for cT1 renal tumors. Methods: 2526 patients with cT1N0M0 renal tumors treated with either PN or radical nephrectomy at 10 European centres in the last decade were included in the analysis. Joinpoint regression analysis was used to identify significant changes over time in linear slope of the trend for each center. The correlation between yearly caseload and the slopes was assessed with the non-parametric Spearman test. Coincident pairwise tests and regression analyses were used to generate and compare the trends of high-volume (HV), mid-volume (MV) and low-volume (LV) groups. Results: Yearly caseload was significantly associated with increased use of PN (R = 0.69, p = 0.028). The utilization rate of PN was stable at LV centres (p = 0.67, p = 0.7, p = 0.76, for cT1, cT1a, and cT1b tumors, respectively), while increased significantly at MV (p = 0.002, 0.0005 and 0.007, respectively) and HV centers (all p < 0.0001). Regression analysis confirmed the trends for HV and MV as significantly different from those observed in LV centres (all p ≤ 0.002) and highlighted significant differences also between MV and HV centres (all p ≤ 0.03). Conclusions: We confirmed the association between caseload and the use of PN for cT1 tumors. Our findings suggest that a minimum caseload might turn the tide also in LV centres while a selective referral to HV centers for cT1b tumors should be considered.